Antioxidant and enzyme-inhibitory properties of sesame seed protein fractions and their isolate and hydrolyzate. Issue 1 (1st January 2021) - Idowu, Atinuke O.; Famuwagun, Akinsola A.; Fagbemi, Tayo, N.; Aluko, Rotimi E.
ABSTRACT: Sesame seed was defatted and subsequently fractionated into albumin, globulin, glutelin and prolamin. The defatted flour was also subjected to alkaline solubilization and acid precipitation to obtain protein isolate. The sesame seed protein isolate was hydrolyzed using a combination of pepsin and pancreatin to produce the protein hydrolyzate. The defatted flour, protein fractions, isolate and hydrolyzate were evaluated for their amino acid profiles as well as in vitro antioxidant and enzyme inhibitory activities. The results showed that the glutelin fraction had higher amounts of essential amino acid (38.1%) when compared with albumin (35.6%), globulin (31.3%), prolamin (37.1%), protein isolate (37.1%) and protein hydrolyzate (36.7%). The defatted flour exhibited the strongest DPPH radical scavenging activity while only the globulin, isolate and hydrolyzate exhibited superoxide radical scavenging activity. The defatted flour also had the strongest hydroxyl radical scavenging activity of 91.79%, although lower than the 95.93% for the control peptide (glutathione). The hydrolyzate had the strongest metal chelating activity (75.53%), while the isolate had the highest ferric antioxidant reducing power. The albumin was the most effective inhibitor of angiotensin converting enzyme and α-amylase with values of 30.04% and 29.44%, respectively. In contrast, renin activity was strongly inhibited (89.87%) by the isolate but acetylcholinesterase was weakly inhibited by the hydrolyzate (16.89%) and prolamin (16.29%). We conclude that the defatted flour and protein products are potential ingredients that could be incorporated into foods to extend shelf-life but also with potential bioactive properties.